Controlling the flight of the discus, part two - Neighbour, B. (Track & field coaches review, 2000)
This article continuous the examination of the interaction of discus release parameters, wind conditions, design and weight characteristics, along with some pre-release technical considerations necessary to optimizing flight range. All details assume releases by right-handed throwers.